2007
DOI: 10.4049/jimmunol.179.5.2758
|View full text |Cite
|
Sign up to set email alerts
|

CD4+ T Cell-Specific Deletion of IL-4 Receptor α Prevents Ovalbumin-Induced Anaphylaxis by an IFN-γ-Dependent Mechanism

Abstract: IL-4Rα-mediated STAT6 activation serves an essential role in various animal models of allergy and asthma at both the sensitization and effector phases. IL-4 and IL-13 signaling via the IL-4Rα chain exacerbates murine anaphylaxis, but the cell-specific requirements for IL-4Rα expression are unclear. The purpose of this study was to elucidate the mechanisms of systemic anaphylaxis to OVA in gene-targeted mice with a deletion of the IL-4Rα chain in the macrophage/neutrophil or CD4+ T lymphocyte population. Result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 49 publications
1
14
0
Order By: Relevance
“…25 Our observation confirmed that mast cells in human colonic tissue express Fc␥RI, but we did not detect the other two types of Fc␥R in colonic mucosa. The differences between those studies and our observation can be local microenvironmentdependent.…”
Section: Discussionsupporting
confidence: 79%
“…25 Our observation confirmed that mast cells in human colonic tissue express Fc␥RI, but we did not detect the other two types of Fc␥R in colonic mucosa. The differences between those studies and our observation can be local microenvironmentdependent.…”
Section: Discussionsupporting
confidence: 79%
“…Control animals received PBS. For induction of endogenous OVA-specific T H 2 cells, DO11.10 mice were sensitized as previously described 19 and challenged with OVA protein, followed by Pam2 injection. Ear thickness was measured with a micrometer (Kroeplin, Schl€ uchtern, Germany) and expressed as a change in ear thickness after treatment.…”
Section: Ovalbumin Sensitization and Adoptive T-cell Transfermentioning
confidence: 99%
“…Infection of these mice with Leishmania major indicated that non-IL-4-responsive CD4 ϩ T cells can launch aspects of a TH2 response (30). Additionally, in ovalbumin-induced anaphylaxis (a TH2-associated pathology) T-cell TH2 cytokine secretion appears to be unaffected by IL-4R␣ CD4 ϩ T-cell expression (28). Together, these findings demonstrate that IL-4R␣ expression on CD4 ϩ T cells is not essential for generation of a TH2 immune response.…”
mentioning
confidence: 99%